TEACHING READING COMPREHENSION THROUGH NUMBERED HEADS TOGETHER TO THE ELEVENTH GRADE STUDENTS OF SMA NURUL AMAL PALEMBANG - Ana Theriana (Esteem Journal of English Education Study Programme, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  The formulation of the problem of this study was â€œis it effective to use Numbered Heads Together in teaching reading comprehension to the eleventh grade students of SMA Nurul Amal Palembangâ€. The objective of this study was to find out whether or not it was effective to teach reading comprehension through numbered heads together to the eleventh grade students of SMA Nurul Amal Palembang.This study used pre-experimental method. The data were collected through written test. Then they were analyzed by using matched t-test. The population of the study wass all of the eleventh grade students of SMA Nurul Amal Palembang in the academic of 2018/2019. The sample were 40 students taken by using convenience sampling.It prove that the studentsâ€™ score in post-test was higher than pre-test. From the data of analysis above, it can be stated that teaching reading comprehenison through numbered heads together to the eleventh grade students of SMA Nurul Amal Palembang was effective.Keyword:teaching, reading, numbered heads